●✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎❀✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎●
Hi my lil bunny!
❧⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯☙
![-6*f(-3)-5*g(-7)](https://tex.z-dn.net/?f=-6%2Af%28-3%29-5%2Ag%28-7%29)
Steps : <u>3</u>
Apply rule : ![- (-a) = a](https://tex.z-dn.net/?f=-%20%28-a%29%20%3D%20a)
![= 6f * 3 + 5g * 7](https://tex.z-dn.net/?f=%3D%206f%20%2A%203%20%2B%205g%20%2A%207)
Multiply the numbers : ![6 * 3 = 18](https://tex.z-dn.net/?f=6%20%2A%203%20%3D%2018)
![= 18f + 5 * 7g](https://tex.z-dn.net/?f=%3D%2018f%20%2B%205%20%2A%207g)
Multiply the numbers : ![5 * 7 = 35](https://tex.z-dn.net/?f=5%20%2A%207%20%3D%2035)
![= 18f + 35g](https://tex.z-dn.net/?f=%3D%2018f%20%2B%2035g)
❧⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯☙
●✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎❀✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎●
Have a great day/night!
❀*May*❀
The answer is Associative
Answer:
f(10) = - 26
Step-by-step explanation:
To evaluate f(10), substitute x = 10 into f(x), that is
f(10) = 4 - 3(10) = 4 - 30 = - 26